The ball room guide, being a compendium of the theory, practice, and etiquette of dancing, embracing the newest quadrilles, polkas, waltzes, schottisches, &c., also, the Meyen quadrille - Meyen, H. (Henry) (New York, E. & J. Magnus, 1852)
This manual begins, as do others of the period, with a general introduction that covers the necessity of dancing and a brief history of dance. Declaring that bodily exercise "drives away sorrow and care," the author asks, "how is it that there are men malicious enough to condemn this innocent pastime?" (p. 12). The manual continues with ten rules to be observed at balls, duties of managers, and seven rules for the German cotillon (a series of dance games). While Meyer gives figures for quadrilles and directions for fourteen German cotillon figures, his descriptions of round dances are vague. For example, he notes that the polka "is either danced in a circle ... or at variety, eight bars to the right and eight bars to the left ..." (pg. 23).
Available also through the Library of Congress Web site as facsimile page images and full text.
Keywords: Ballroom dancing -- Handbooks, manuals, etc; Dance Instruction and Technical Manuals